Towards Mannosylerythritol Lipids (MELs) for Bioremediation: Effects of NaCl on M. antarcticus Physiology and Biosurfactant and Lipid Production; Ecotoxicity of MELs - Petar Keković; Margarida Borges; Nuno Torres Faria; Frederico Castelo Ferreira (Journal of Marine Science and Engineering, 2022)
Mannosylerythritol lipids (MELs) are a group of biosurfactants with a wide range of potential applications, due to their excellent tensioactive properties, biocompatibility, and biodegradability. One of the envisioned uses for MELs is in bioremediation in marine and terrestrial environments. However, knowledge regarding their ecotoxicity is limited. The current costs of production for this biosurfactant are too high to make it competitive in the surfactant market. In an effort to facilitate the use of MELs for marine bioremediation purposes, their production using sea water in medium formulation was explored. Cells were exposed to different levels of NaCl during fermentation, and the effects of increased salinity on the cells and their performance was monitored. In addition, cells were briefly exposed to an osmotic shock, by introducing pure NaCl into the broth, to measure their physiological response. Although the overall effect of NaCl in the medium was negative, cells produced more lipases in these stress conditions. Furthermore, the changes triggered by the osmotic shock caused changes in the cell surface and affected their hydrophobicity, reducing the levels of MELs adsorbed to the cells, which in turn led to an increase in formation of MEL-rich beads. Marine-level salinity (3.5%) was found to be sufficient to enable production of MELs in unsterile conditions and inhibited an introduced bacterial contaminant. Finally, the toxicity levels of MELs to a model marine organism and plant model were lower than other biosurfactants and that of a commercial chemical dispersant used for bioremediation.